2017
DOI: 10.1002/jor.23806
|View full text |Cite
|
Sign up to set email alerts
|

Human prosthetic joint infections are associated with myeloid‐derived suppressor cells (MDSCs): Implications for infection persistence

Abstract: Animal models of PJI have revealed a critical role for MDSCs and IL-10 in promoting infection persistence; however, whether this population is prevalent during human PJI and across distinct bacterial pathogens remains unknown. This study has identified that granulocytic-MDSC infiltrates are unique to human PJIs caused by distinct bacteria, which are not associated with aseptic loosening of prosthetic joints. Better defining the immune status of human PJIs could lead to novel immune-mediated approaches to facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 45 publications
6
67
0
2
Order By: Relevance
“…The finding that transcriptional profiles of biofilm-associated MDSCs and PMNs were very similar (i.e., only 297 differentially expressed genes) provided evidence supporting the granulocytic nature of MDSCs (i.e., G-MDSCs) as opposed to M-MDSCs. This is in agreement with what is observed during human prosthetic joint infection, where significant increases in the numbers of G-MDSCs are observed compared to aseptic revisions (38). Further evidence of the functional importance of MDSCs compared to PMNs was demonstrated in our previous study, where treatment of mice with a Ly6G antibody, which depletes both MDSCs and PMNs, led to significant reductions in biofilm burdens (12).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding that transcriptional profiles of biofilm-associated MDSCs and PMNs were very similar (i.e., only 297 differentially expressed genes) provided evidence supporting the granulocytic nature of MDSCs (i.e., G-MDSCs) as opposed to M-MDSCs. This is in agreement with what is observed during human prosthetic joint infection, where significant increases in the numbers of G-MDSCs are observed compared to aseptic revisions (38). Further evidence of the functional importance of MDSCs compared to PMNs was demonstrated in our previous study, where treatment of mice with a Ly6G antibody, which depletes both MDSCs and PMNs, led to significant reductions in biofilm burdens (12).…”
Section: Discussionsupporting
confidence: 91%
“…Remarkably, EdU labeling revealed that approximately 50% of MDSCs associated with biofilms at day 7 postinfection arise from local division. The mediators responsible for this are not known; however, the levels of several factors implicated in MDSC expansion are elevated in the biofilm milieu, including granulocyte colony-stimulating factor (G-CSF), IL-6, and vascular endothelial growth factor (VEGF) (12,38). Interestingly, a mature F4/80 ϩ macrophage population is limited during S. aureus orthopedic biofilm infection, even though monocytes display significantly increased expression levels of several cell cycle genes and are dividing at the site of infection, as shown by EdU labeling.…”
Section: Discussionmentioning
confidence: 99%
“…This model reflects biofilm growth as demonstrated by us and others using SEM and H&E staining [13,14,47,[76][77][78]. In addition, immunophenotyping of patients with PJI, many of which were diagnosed with S. aureus, has revealed similar leukocyte infiltrates as observed in the mouse model [13,22], supporting its translational utility. Briefly, mice were anesthetized with ketamine/xylazine (100 mg/kg and 5 mg/kg, respectively) and the skin was disinfected with povidone-iodine.…”
Section: Mouse Model Of S Aureus Orthopedic Implant Biofilm Infectionsupporting
confidence: 66%
“…Therefore, the immune polarization state of monocytes and MFs plays a key role in dictating biofilm persistence and this is influenced, in part, by MDSC-derived factors. Our prior work has identified the presence of monocyte, MDSC, and neutrophil (PMN) infiltrates in human PJI, revealing similarities between the mouse model and human infection [22].…”
Section: Introductionmentioning
confidence: 85%
“…46,47 It is well-known that MDSCs are potent inhibitors of T-cell activation in S. aureus infection. [48][49][50] We previously showed that S. aureus biofilm increased MDSC expansion and subsequent T-cell suppression. 25 Compared to non-MDSC controls, coculture with MDSCs decreased T-cell proliferation by 41.4%, while treatment with biofilm reduced the proliferation by up to 62.8% ( Figure 5).…”
Section: Effects Of Curn On S Aureus Biofilmtreated Mdsc and T-cell mentioning
confidence: 99%